Fireworks at the FBI - Roy, Ron, 1940-; Bush, Timothy (New York : Random House, 2006)
As they leave a Fourth of July celebration with the President of the United States, KC and Marshall see unauthorized fireworks at the FBI Building and decide to unmask the culprit and his plans for blackmail.
"A Stepping Stone Book."
RL: 2.8.
006-009.
Accelerated Reader AR
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Extortion -- Fiction; Mystery and detective stories; Washington (D.C.) -- Fiction